The economy for the common good as an alternative economic model for a more sustainable and fair future? Ananalysis of the implementation in the Bavarian towns Kirchanschöring and Postbauer-Hengn - Kroemer, Maximilian (Momentum Quarterly, 2025)
In 2010, the Austrian activist Christian Felber published his concept of an economic order geared towards the common good. In Bavaria, the municipalities of Kirchanschöring and Postbauer-Heng published a common good balance sheet based on Felber’s suggestion. In this research work, the certification process in Kirchanschöring and Postbauer-Heng was examined based on the policy cycle (political science phase modell for the analysis of political processes) regarding their implementation strategies. Furthermore, the success of the respective processes was evaluated. It was found that the processes involved in preparing the balance sheet in Kirchanschöring and Postbauer-Heng are mostly similar. The inclusion of the political level in the respective implementation phases was identified as a central difference. In both communities, obstacles on the way to certification were overcome and follow-up measures were initiated, which is why both projects can be viewed as successes.